The effectiveness of rambutan (Nephelium lappaceum L.) extract in stabilization of sunflower oil under accelerated conditions - Sia, Winne Chiaw Mei; Ismail, Amin; Mohd. Esa, Norhaizan; Akowuah, Gabriel Akyirem; Ho, Chun Wai; Yim, Hip Seng (MDPI, 2014)
The oxidative properties of sunflower oil supplemented with rambutan extract, (crude extract and its fractionated fraction, SF II) in comparison with synthetic antioxidant were investigated. The supplemented sunflower oils were stored under accelerated conditions for 24 days at 60 °C. For every 6-day interval, the oxidative properties of the supplemented sunflower oil were evaluated based on the following tests, namely peroxide value, p-anisidine value, Thiobarbituric Acid Reactive Substances (TBARS) assay, iodine value and free fatty acids. The total oxidation (TOTOX) values were also calculated based on the peroxide values and p-anisidine values. Rambutan extract is a potential source of antioxidant. The oxidative activities of the extracts at all concentrations were significantly (p < 0.05) higher than the control. Generally, the partially fractionated fraction was more effective than the crude extract. With a 2-year storage period at ambient temperature, the fractionated fraction of the extract, SF II at 300 ppm, was observed to work more effectively than the synthetic antioxidant, t-Tocopherol, and it possessed a protective effect comparable with butylatedhydrioxynanisole (BHA). Therefore, rambutan extract could be used as a potential alternative source of antioxidant in the oil industry or other fat-based products to delay lipid oxidation.